2020
DOI: 10.3390/jcm9010186
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and Psoriatic Arthritis Cardiovascular Disease Endotypes Identified by Red Blood Cell Distribution Width and Mean Platelet Volume

Abstract: In a subset of psoriasis (PsO) and psoriatic arthritis (PsA) patients, the skin and/or joint lesions appear to generate biologically significant systemic inflammation. Red cell distribution width (RDW) and mean platelet volume (MPV) are readily available clinical tests that reflect responses of the bone marrow and/or plasma thrombogenicity (e.g., inflammation), and can be markers for major adverse cardiac events (MACE). We aimed to evaluate if RDW and MPV may be employed as inexpensive, routinely obtained biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 53 publications
1
50
0
Order By: Relevance
“…This disease was considered as a solely dermatological condition, while recent studies have linked psoriasis to many comorbidities namely obesity, cardiometabolic events, diabetes mellitus type 2 (DM type 2), lipid disturbances, and liver dysfunctions [1][2][3]. Further investigations have highlighted a higher risk of hypertension, metabolic syndrome (MS), or DM in association with the severity of psoriasis [1][2][3][4][5][6]. The morbidity of psoriatic patients is significantly higher compared with the population, which is due to the increased risk of cardiovascular events, mainly myocardial infarction (MI) and thromboembolic disorders [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This disease was considered as a solely dermatological condition, while recent studies have linked psoriasis to many comorbidities namely obesity, cardiometabolic events, diabetes mellitus type 2 (DM type 2), lipid disturbances, and liver dysfunctions [1][2][3]. Further investigations have highlighted a higher risk of hypertension, metabolic syndrome (MS), or DM in association with the severity of psoriasis [1][2][3][4][5][6]. The morbidity of psoriatic patients is significantly higher compared with the population, which is due to the increased risk of cardiovascular events, mainly myocardial infarction (MI) and thromboembolic disorders [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations have highlighted a higher risk of hypertension, metabolic syndrome (MS), or DM in association with the severity of psoriasis [1][2][3][4][5][6]. The morbidity of psoriatic patients is significantly higher compared with the population, which is due to the increased risk of cardiovascular events, mainly myocardial infarction (MI) and thromboembolic disorders [4][5][6][7]. However, the exact etiology of atherothrombotic events in psoriasis is still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, inflammatory parameters, such as CRP and ESR, actually useful to assess and follow up the activity of autoimmune diseases; a novel index for inflammation, RDW, may be also useful to assess the activity of autoimmune diseases. Previous studies have shown that RDW was associated with the increased severity of inflammatory bowel disease (IBD), SLE [9,10], RA [11], and psoriatic arthritis [12,13]. Another recent study has also concluded that RDW was increased in patients with SLE [14].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of psoriasis is currently estimated to be as high as 2-3% worldwide, becoming a serious global problem. [3][4][5] Moreover, it is also associated with many comorbidities such as psoriasis arthritis, 6 metabolic syndrome 7 and cardiovascular disease, 8 which brings huge health and economic burden to patients. Although various immune abnormalities have been proposed to be involved in the pathogenesis of psoriasis, 9 oxidative stress is also believed to play a pivotal role in the pathophysiological mechanism.…”
Section: Introductionmentioning
confidence: 99%